BIBLIOMETRIC ANALYSIS OF DUAL CAREERS ATHLETE (2012-2023) - Septina, Trisha Aryanti; Hidayat, Yusuf; Kusnaedi, Kusnaedi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Dual career athlete is the definition of a situation where an athlete pursues two career paths simultaneously. This study aims to analyze dual career athlete-related research published in 2012-2023 using bibliometric analysis methods. This study describes the structure and trends using scientific mapping and analysis on dual career athlete publications. The bibliometric analysis carried out produces trends in research years, the most published authors, countries conducting research, keyword analysis and finally trend analysis of themes and topics. The findings in this study are that in 2012 there was one article about dual career athletes. There are 191 documents published by 84 journals with 160 authors, there are 45 countries that conduct research on dual career athletes with the most publications by Spain, namely 45 articles. The author who published the most articles is Ryba, T.V., which is 13 articles. The increase in dual career athlete research occurred in 2020, namely during the covid-19 pandemic. Then it increased and the peak of the most research was in 2022, namely 35 studies.